Titanium-based composite material and method of making same, titanium-based article
Patent Information
- Application Number
- CN202311609306.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-29
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-11-29
AI Technical Summary
然而,将碳化钛陶瓷粉添加到钛合金基体的传统方法制得的钛基复合材料的塑性较差
[0027]上述钛基复合材料的制备方法,通过采用第一脉冲电流辅助成型处理,并控制第一脉冲电流辅助成型处理的电流强度,混合粉末中石墨烯与钛材料的接触面原位生成纳米碳化钛,有效提升纳米碳化钛陶瓷弥散相与钛材料的化学结合及均匀化分布,从而有效提升钛基复合材料的延伸率,即有效提升钛基复合材料的塑性;同时,第一脉冲电流辅助成型处理在原位生成纳米碳化钛的基础上,还保留有石墨烯本身的二维结构,石墨烯和碳化钛两种增强体共同提升钛基复合材料的抗拉强度、屈服强度和弹性模量;进一步通过将第一脉冲电流辅助成型处理得到的钛基复合材料前驱体进行第二脉冲电流辅助成型处理,并控制第二脉冲电流辅助成型处理的电流强度,在该电流强度下,使温度达到钛基复合材料前驱体的相变点,促进钛基复合材料前驱体的组织形貌发生变化,以及有效细化钛基复合材料前驱体的组织,并进一步对第二脉冲电流辅助成型处理得到的钛基复合材料中间体进行热塑性变形处理,各步骤和参数共同配合作用,有效提升钛基复合材料的塑性、抗拉强度、屈服强度和弹性模量。
Smart Images

Figure CN117867322B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of materials technology, and in particular to a titanium-based composite material and its preparation method, as well as titanium-based products. Background Technology
[0002] Titanium alloys possess advantages such as low density, high specific strength, good heat and corrosion resistance, and excellent biocompatibility, making them promising for applications in both defense and civilian industries. They are primarily used in military and civilian aircraft, aerospace engines, spacecraft, and satellite casing connectors. Considering the demands for energy conservation and weight reduction, further improving the mechanical properties of titanium alloys is particularly important. Dispersion strengthening with reinforcing phase particles is an effective method for improving the mechanical properties of titanium-based composites. However, titanium-based composites prepared by the traditional method of adding titanium carbide ceramic powder to a titanium alloy matrix exhibit poor plasticity.
[0003] Therefore, it is necessary to improve traditional technologies. Summary of the Invention
[0004] Based on this, this application provides a titanium-based composite material with good tensile strength, yield strength and plasticity, a preparation method thereof, and titanium-based products.
[0005] The technical solution to the above-mentioned technical problems in this application is as follows.
[0006] The first aspect of this application provides a method for preparing a titanium-based composite material, comprising the following steps:
[0007] A titanium-based composite material precursor is obtained by subjecting a mixed powder containing graphene and titanium materials to a first pulse current-assisted molding process; the current intensity of the first pulse current-assisted molding process is 5 A to 10 A.
[0008] The titanium-based composite material precursor is subjected to a second pulse current-assisted molding treatment to obtain a titanium-based composite material intermediate; the current intensity of the second pulse current-assisted molding treatment is 10 A to 20 A.
[0009] The titanium-based composite intermediate was subjected to thermoplastic deformation treatment.
[0010] In some embodiments, in the method for preparing titanium-based composite materials, the current intensity of the second pulse current assisted molding treatment is greater than the current intensity of the first pulse current assisted molding treatment.
[0011] In some embodiments, the preparation method of the titanium-based composite material involves a first pulse current-assisted molding process lasting 60 s to 300 s.
[0012] In some embodiments, the preparation method of the titanium-based composite material involves a second pulsed current-assisted molding process lasting 300 s to 420 s.
[0013] In some embodiments, the preparation method of the titanium-based composite material satisfies at least one of the following features (1) to (3):
[0014] (1) The external compressive stress of the first pulse current assisted molding process and the second pulse current assisted molding process are independently 10 MPa~60 MPa;
[0015] (2) The pulse power supply frequencies of the first pulse current assisted molding process and the second pulse current assisted molding process are independently 100 Hz to 300 Hz;
[0016] (3) The duty cycle of the pulse power supply for the first pulse current assisted molding process and the second pulse current assisted molding process is 0.1~0.5 independently.
[0017] In some embodiments, in the preparation method of the titanium-based composite material, the graphene accounts for 0.3 wt% to 3 wt% of the mass of the titanium-based composite material.
[0018] In some embodiments, the titanium material used in the preparation method of the titanium-based composite material includes at least one of pure titanium and titanium alloys.
[0019] In some embodiments, the preparation of the mixed powder in the method for preparing the titanium-based composite material includes the following steps:
[0020] The graphene powder, titanium powder, and organic solvent are mixed and stirred, then dried to obtain the mixed powder.
[0021] In some embodiments, in the method for preparing the titanium-based composite material, the thermoplastic deformation treatment satisfies at least one of the following characteristics (1) to (2):
[0022] (1) The thermoplastic deformation treatment method includes one of hot extrusion, forging and rolling;
[0023] (2) The thermoplastic deformation treatment is carried out by forging, the forging temperature is 1000℃~1100℃, and the forging ratio is 3~5.
[0024] The second aspect of this application provides a titanium-based composite material, which is prepared using the method for preparing titanium-based composite materials provided in the first aspect.
[0025] A third aspect of this application provides a titanium-based article, including the titanium-based composite material provided in the second aspect.
[0026] Compared with existing technologies, the preparation method of titanium-based composite materials in this application has the following advantages:
[0027] The above-mentioned method for preparing titanium-based composite materials involves employing a first pulse current-assisted molding process and controlling the current intensity of this process. This process generates nano-titanium carbide in situ at the interface between graphene and titanium in the mixed powder, effectively enhancing the chemical bonding and uniform distribution of the nano-titanium carbide ceramic dispersed phase with the titanium material. This, in turn, effectively improves the elongation of the titanium-based composite material, thus enhancing its plasticity. Simultaneously, the first pulse current-assisted molding process, while generating nano-titanium carbide in situ, also retains the two-dimensional structure of graphene itself. The two reinforcing agents, graphene and titanium carbide, together enhance the tensile strength, yield strength, and... Elastic modulus; further, by subjecting the titanium-based composite precursor obtained from the first pulse current assisted molding treatment to a second pulse current assisted molding treatment, and controlling the current intensity of the second pulse current assisted molding treatment, the temperature is made to reach the phase transition point of the titanium-based composite precursor, which promotes changes in the microstructure of the titanium-based composite precursor and effectively refines the microstructure of the titanium-based composite precursor. In addition, the titanium-based composite intermediate obtained from the second pulse current assisted molding treatment is subjected to thermoplastic deformation treatment. The various steps and parameters work together to effectively improve the plasticity, tensile strength, yield strength and elastic modulus of the titanium-based composite material. Attached Figure Description
[0028] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0029] Figure 1 This is a high-resolution TEM image of the titanium-based composite material prepared in Example 1. Detailed Implementation
[0030] Reference will now be made to detailed embodiments of the present invention, one or more of which are described below. Each example is provided for explanation and not for limitation of the invention. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to the invention without departing from its scope or spirit. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.
[0031] Therefore, this invention is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the invention are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0033] The terms “comprising,” “including,” or any other variations thereof are intended to cover a non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element preceded by the phrase “comprising one…” does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. The indefinite articles “a” and “an” preceding an element or component of the invention are not restrictive in terms of the number of elements or components (i.e., the number of times they appear). Therefore, “an” or “an” should be interpreted as including one or at least one, and singular elements or components also include plural forms, unless the quantity clearly refers only to the singular. “A plurality” means at least two, such as two, three, etc., unless otherwise expressly specified.
[0034] The weights of the relevant components mentioned in the embodiments of this invention can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this invention is within the scope disclosed in the embodiments of this invention. Specifically, the weights mentioned in the embodiments of this invention can be well-known units of mass in the chemical industry, such as μg, mg, g, and kg.
[0035] Unless otherwise shown or indicated in the operational embodiments, all figures used to represent the amounts, physicochemical properties, etc., of ingredients in the specification and claims are to be understood to be adjusted by the term "about" in all cases. For example, therefore, unless stated to the contrary, the numerical parameters listed in the foregoing specification and appended claims are approximations, and those skilled in the art can appropriately modify these approximations to obtain the desired characteristics by utilizing the teachings disclosed herein. The use of numerical ranges indicated by endpoints includes all numbers within that range and any range within that range; for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4, and 5, etc.
[0036] Analysis suggests that the poor plasticity of titanium-based composite materials prepared by the traditional method of adding titanium carbide ceramic powder to a titanium alloy matrix is due to the poor bonding between titanium carbide and the titanium matrix.
[0037] One embodiment of this application provides a method for preparing a titanium-based composite material, comprising the following steps:
[0038] Step S10: The mixed powder containing graphene and titanium materials is subjected to a first pulse current assisted molding treatment to obtain a titanium-based composite material precursor; the current intensity of the first pulse current assisted molding treatment is 5 A~10 A.
[0039] By employing a first pulse current-assisted molding process and controlling the current intensity of the first pulse current-assisted molding process, nano-titanium carbide is generated in situ at the contact surface between graphene and titanium material in the mixed powder. This effectively enhances the chemical bonding and uniform distribution of the nano-titanium carbide ceramic dispersed phase with the titanium material, thereby effectively improving the elongation of the titanium-based composite material, i.e., effectively improving the plasticity of the titanium-based composite material. At the same time, the first pulse current-assisted molding process retains the two-dimensional structure of graphene itself on the basis of in-situ generation of nano-titanium carbide. The two reinforcements, graphene and titanium carbide, jointly improve the tensile strength, yield strength and elastic modulus of the titanium-based composite material.
[0040] It is understood that the current intensity of the first pulse current-assisted molding process includes, but is not limited to, 5 A, 6 A, 7 A, 8 A, 9 A, and 10 A; in some examples, it can be any two of these point values as the end values, and the same applies below.
[0041] In some of these examples, in step S10, the current intensity of the first pulse current-assisted molding process is 5 A to 8 A.
[0042] In some of these examples, in step S10, the external compressive stress of the first pulse current-assisted molding process is 10 MPa to 60 MPa.
[0043] It is understood that the external compressive stress of the first pulse current assisted molding process includes, but is not limited to, 10 MPa, 12 MPa, 15 MPa, 18 MPa, 20 MPa, 22 MPa, 125 MPa, 28 MPa, 30 MPa, 32 MPa, 35 MPa, 38 MPa, 40 MPa, 42 MPa, 45 MPa, 48 MPa, 50 MPa, 52 MPa, 55 MPa, 58 MPa, and 60 MPa.
[0044] In some of these examples, in step S10, the pulse power supply frequency of the first pulse current-assisted molding process is 100 Hz to 300 Hz.
[0045] It is understood that the pulse power supply frequency for the first pulse current-assisted molding process includes, but is not limited to, 100 Hz, 120 Hz, 140 Hz, 150 Hz, 160 Hz, 180 Hz, 200 Hz, 220 Hz, 240 Hz, 250 Hz, 260 Hz, 280 Hz, and 300 Hz.
[0046] In some of these examples, in step S10, the duty cycle of the pulse power supply for the first pulse current-assisted molding process is 0.1 to 0.5.
[0047] It is understood that the duty cycle of the pulse power supply for the first pulse current-assisted molding process includes, but is not limited to, 0.1, 0.2, 0.3, 0.4, and 0.5.
[0048] In some of these examples, in step S10, the duration of the first pulse current-assisted molding process is 60 s to 300 s.
[0049] It is understood that the time for the first pulse current-assisted molding process includes, but is not limited to, 60 s, 80 s, 100 s, 120 s, 150 s, 180 s, 200 s, 220 s, 250 s, 280 s, and 300 s.
[0050] In some of these examples, in step S10, the mass of graphene accounts for 0.3 wt% to 3 wt% of the mass of the titanium-based composite material.
[0051] It is understood that the percentage of graphene in the mass of the titanium-based composite material includes, but is not limited to, 0.3 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, 1.2 wt%, 1.5 wt%, 1.8 wt%, 2 wt%, 2.2 wt%, 2.5 wt%, 2.8 wt%, and 3 wt%.
[0052] In some of these examples, in step S10, the mass of graphene accounts for 0.3 wt% to 2 wt% of the mass of the titanium-based composite material.
[0053] In some of these examples, in step S10, the mass of graphene accounts for 0.5 wt% to 2 wt% of the mass of the titanium-based composite material.
[0054] In some of these examples, in step S10, the mass of graphene accounts for 0.8 wt% to 1.5 wt% of the mass of the titanium-based composite material.
[0055] In some of these examples, in step S10, the titanium material includes at least one of pure titanium and titanium alloys.
[0056] Furthermore, titanium alloys include TC4 titanium alloy.
[0057] In some of these examples, step S10, the preparation of the mixed powder includes the following steps:
[0058] After mixing and stirring graphene powder, titanium powder and organic solvent, the mixture is dried to obtain a mixed powder.
[0059] Furthermore, organic solvents include alcohol.
[0060] In some of these examples, in step S10, the total mass ratio of graphene powder and titanium powder to alcohol is 1:(0.5~5).
[0061] It is understandable that the mass ratio of the total mass of graphene powder and titanium powder to the mass of alcohol includes, but is not limited to, 1:0.5, 1:1, 1:2, 1:3, 1:4, and 1:5.
[0062] Furthermore, mechanical stirring is used for mixing.
[0063] Furthermore, the mixing and stirring time is 1 h to 2 h.
[0064] Furthermore, the drying conditions include vacuum drying at 50℃~70℃.
[0065] It is understood that the temperature for vacuum drying includes, but is not limited to, 50℃, 60℃, and 70℃.
[0066] It is understood that this application does not limit the size of graphene powder and titanium material powder.
[0067] In some of these examples, in step S10, the graphene powder has a sheet diameter of 0.5 μm to 50 μm.
[0068] It is understood that the sheet diameter of graphene powder includes, but is not limited to, 0.5 μm, 1 μm, 10 μm, 20 μm, 30 μm, 40 μm, and 50 μm.
[0069] In some of these examples, in step S10, the particle size of the titanium material powder is 1 μm to 150 μm.
[0070] It is understood that the particle size of titanium material powder includes, but is not limited to, 1 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, and 150 μm.
[0071] Step S20: The titanium-based composite material precursor obtained in step S10 is subjected to a second pulse current assisted molding treatment to obtain a titanium-based composite material intermediate; the current intensity of the second pulse current assisted molding treatment is 10 A~20 A.
[0072] It is understood that the current intensity of the second pulse current assisted molding process includes, but is not limited to, 10 A, 11 A, 12 A, 13 A, 14 A, 15 A, 16 A, 17 A, 18 A, 19 A, and 20 A.
[0073] In some of these examples, in step S20, the current intensity of the second pulse current-assisted molding process is 15 A to 20 A.
[0074] In some of these examples, the current intensity of the second pulse current-assisted molding process is greater than that of the first pulse current-assisted molding process in the preparation method of the titanium-based composite material.
[0075] In some of these examples, the current intensity of the first pulse current-assisted molding treatment is 5 A to 8 A, and the current intensity of the second pulse current-assisted molding treatment is 15 A to 20 A.
[0076] In some of these examples, the current intensity of the first pulse current-assisted molding treatment is 5 A to 6 A, and the current intensity of the second pulse current-assisted molding treatment is 18 A to 20 A.
[0077] In some of these examples, the current intensity of the first pulse current-assisted molding process is 5 A, and the current intensity of the second pulse current-assisted molding process is 20 A.
[0078] In some of these examples, in step S20, the external compressive stress of the second pulse current-assisted molding process is 10 MPa to 60 MPa.
[0079] It is understood that the external compressive stress of the second pulse current assisted molding process includes, but is not limited to, 10 MPa, 12 MPa, 15 MPa, 18 MPa, 20 MPa, 22 MPa, 125 MPa, 28 MPa, 30 MPa, 32 MPa, 35 MPa, 38 MPa, 40 MPa, 42 MPa, 45 MPa, 48 MPa, 50 MPa, 52 MPa, 55 MPa, 58 MPa, and 60 MPa.
[0080] In some of these examples, the compressive stress applied during the second pulse current-assisted molding process is the same as that applied during the first pulse current-assisted molding process in the preparation method of the titanium-based composite material.
[0081] In some of these examples, in step S20, the pulse power supply frequency for the second pulse current-assisted molding process is 100 Hz to 300 Hz.
[0082] It is understood that the pulse power supply frequency for the second pulse current-assisted molding process includes, but is not limited to, 100 Hz, 120 Hz, 140 Hz, 150 Hz, 160 Hz, 180 Hz, 200 Hz, 220 Hz, 240 Hz, 250 Hz, 260 Hz, 280 Hz, and 300 Hz.
[0083] In some of these examples, the pulse power supply frequency of the second pulse current assisted molding treatment is the same as that of the first pulse current assisted molding treatment in the preparation method of the titanium-based composite material.
[0084] In some of these examples, in step S20, the duty cycle of the pulse power supply for the second pulse current-assisted molding process is 0.1 to 0.5.
[0085] It is understood that the duty cycle of the pulse power supply for the second pulse current-assisted molding process includes, but is not limited to, 0.1, 0.2, 0.3, 0.4, and 0.5.
[0086] In some examples, in the preparation method of titanium-based composite materials, the duty cycle of the pulse power supply for the second pulse current-assisted molding process is the same as that for the first pulse current-assisted molding process.
[0087] In some of these examples, in step S20, the duration of the second pulse current-assisted molding process is 300 s to 420 s.
[0088] It is understood that the time for the second pulse current-assisted molding process includes, but is not limited to, 300 s, 320 s, 350 s, 380 s, 400 s, and 420 s.
[0089] It is understandable that the titanium-based composite material obtained in step S20 can be subjected to thermoplastic deformation treatment according to different requirements.
[0090] Step S30: The titanium-based composite intermediate obtained in step S20 is subjected to thermoplastic deformation treatment.
[0091] The above-mentioned method for preparing titanium-based composite materials involves employing a first pulse current-assisted molding process and controlling the current intensity of this process. This process generates nano-titanium carbide in situ at the interface between graphene and titanium in the mixed powder, effectively enhancing the chemical bonding and uniform distribution of the nano-titanium carbide ceramic dispersed phase with the titanium material. This, in turn, effectively improves the elongation of the titanium-based composite material, thus enhancing its plasticity. Simultaneously, the first pulse current-assisted molding process, while generating nano-titanium carbide in situ, also retains the two-dimensional structure of graphene itself. The two reinforcing agents, graphene and titanium carbide, together enhance the tensile strength, yield strength, and... Elastic modulus; further, by subjecting the titanium-based composite precursor obtained from the first pulse current assisted molding treatment to a second pulse current assisted molding treatment, and controlling the current intensity of the second pulse current assisted molding treatment, the temperature is made to reach the phase transition point of the titanium-based composite precursor, which promotes changes in the microstructure of the titanium-based composite precursor and effectively refines the microstructure of the titanium-based composite precursor. In addition, the titanium-based composite intermediate obtained from the second pulse current assisted molding treatment is subjected to thermoplastic deformation treatment. The various steps and parameters work together to effectively improve the plasticity, tensile strength, yield strength and elastic modulus of the titanium-based composite material.
[0092] Meanwhile, pulsed current, as a high-density energy input method, has a unique Joule heating effect that can rapidly heat metal materials in a very short time, and can also effectively avoid the heat loss caused by traditional heating methods.
[0093] In some of these examples, in step S30, the thermoplastic deformation process includes one of hot extrusion, forging, and rolling.
[0094] In some of these examples, step S30 involves thermoplastic deformation by forging.
[0095] In some of these examples, in step S30, the forging temperature is 1000℃~1100℃.
[0096] It is understood that forging temperatures include, but are not limited to, 1000℃, 1020℃, 1050℃, 1080℃, and 1100℃.
[0097] In some of these examples, in step S30, the forging ratio is 3 to 5.
[0098] It is understood that in step S30, the forging ratio of the forging process includes, but is not limited to, 3, 4, and 5.
[0099] In some examples, the preparation method of titanium-based composite materials also includes step S40:
[0100] The material obtained in step S30 is subjected to annealing.
[0101] In some of these examples, the annealing temperature in step S40 is 700°C to 800°C.
[0102] It is understood that in step S40, the annealing temperature includes, but is not limited to, 700℃, 720℃, 750℃, 780℃, and 800℃.
[0103] In some of these examples, the annealing process in step S40 takes 1 to 3 hours.
[0104] It is understood that the annealing time in step S40 includes, but is not limited to, 1 h, 2 h, and 3 h.
[0105] One embodiment of this application provides a titanium-based composite material, which is prepared using the above-described method for preparing titanium-based composite materials.
[0106] The titanium-based composite material prepared by the above method has good plasticity and high tensile strength, yield strength and elastic modulus.
[0107] One embodiment of this application provides the application of the above-described titanium-based composite material in the preparation of titanium-based articles. Another embodiment of this application provides a titanium-based article comprising the above-described titanium-based composite material.
[0108] The aforementioned titanium-based composite materials are used to prepare titanium-based products, which can endow the titanium-based products with high plasticity, tensile strength, yield strength and elastic modulus.
[0109] In some embodiments, titanium-based articles include, but are not limited to, military aircraft, civilian aircraft, aerospace engines, spacecraft, and satellite shell connectors.
[0110] In some embodiments, the titanium-based article may be made of the aforementioned titanium-based composite material, that is, the titanium-based article may be directly prepared using the aforementioned titanium-based composite material. In other embodiments, the titanium-based article may be made of other materials in addition to the aforementioned titanium-based composite material.
[0111] The present application will be described in further detail below with reference to specific embodiments, but the embodiments of the present application are not limited thereto.
[0112] Example 1
[0113] (1) According to the mass of graphene accounting for 1 wt% of the mass of titanium-based composite material, graphene powder, titanium material (TC4 titanium alloy) powder and alcohol (the total mass of graphene powder and titanium material powder to the mass ratio of alcohol is 1:1) are mechanically mixed for 2 h and then vacuum dried at 60℃ to obtain a mixed powder containing graphene and titanium material.
[0114] (2) The mixed powder obtained in step (1) is placed into a pulse current assisted pressing mold and sealed. An external pressure of 60 MPa is applied to perform the first pulse current assisted molding treatment. The pulse current intensity is adjusted to 5 A, the duty cycle is 0.1, the frequency is 100 Hz, and the current is continuously applied for 60 s to obtain the titanium-based composite material precursor. The pulse current intensity is adjusted to 10 A, and the current is continuously applied for 300 s to continue the second pulse current assisted molding treatment on the obtained titanium-based composite material precursor (i.e., in the second pulse current assisted molding treatment, the external pressure is 60 MPa, the duty cycle is 0.1, and the frequency is 100 Hz) to obtain the titanium-based composite material intermediate.
[0115] (3) The titanium-based composite intermediate obtained in step (2) was forged at a forging temperature of 1050℃ and a forging ratio of 4. After forging, it was annealed at 750℃ for 2 h to obtain the titanium-based composite material. Its TEM high-resolution morphology image is shown below. Figure 1 As shown. From Figure 1 It can be seen that graphene retains its two-dimensional structure in the titanium-based composite material, and carbide particles are generated in situ at the interface between graphene and the titanium matrix.
[0116] Example 2
[0117] The example is basically the same as in Example 1, except that step (2) in Example 2 is as follows:
[0118] (2) The mixed powder obtained in step (1) is placed into a pulse current assisted pressing mold and sealed. An external pressure of 60 MPa is applied to perform the first pulse current assisted molding process. The pulse current intensity is adjusted to 10 A, the duty cycle is 0.3, the frequency is 100 Hz, and the current is continuously applied for 60 s to obtain the titanium-based composite material precursor. The pulse current intensity is adjusted to 10 A, and the current is continuously applied for 300 s to continue the second pulse current assisted molding process on the obtained titanium-based composite material precursor (i.e., in the second pulse current assisted molding process, the external pressure is 60 MPa, the duty cycle is 0.3, and the frequency is 100 Hz) to obtain the titanium-based composite material intermediate.
[0119] Example 3
[0120] The example is basically the same as Example 1, except that step (2) of Example 3 is as follows:
[0121] (2) The mixed powder obtained in step (1) is placed into a pulse current assisted pressing mold and sealed. An external pressure of 60 MPa is applied to perform the first pulse current assisted molding process. The pulse current intensity is adjusted to 5 A, the duty cycle is 0.3, the frequency is 100 Hz, and the current is continuously applied for 300 s to obtain the titanium-based composite material precursor. The pulse current intensity is adjusted to 20 A, and the current is continuously applied for 300 s to continue the second pulse current assisted molding process on the obtained titanium-based composite material precursor (i.e., in the second pulse current assisted molding process, the external pressure is 60 MPa, the duty cycle is 0.3, and the frequency is 100 Hz) to obtain the titanium-based composite material intermediate.
[0122] Example 4
[0123] The example is basically the same as Example 1, except that step (2) of Example 4 is as follows:
[0124] (2) The mixed powder obtained in step (1) is placed into a pulse current assisted pressing mold and sealed. An external pressure of 60 MPa is applied to perform the first pulse current assisted molding process. The pulse current intensity is adjusted to 5 A, the duty cycle is 0.5, the frequency is 100 Hz, and the current is continuously applied for 120 s to obtain the titanium-based composite material precursor. The pulse current intensity is adjusted to 15 A, and the current is continuously applied for 420 s to continue the second pulse current assisted molding process on the obtained titanium-based composite material precursor (i.e., in the second pulse current assisted molding process, the external pressure is 60 MPa, the duty cycle is 0.5, and the frequency is 100 Hz) to obtain the titanium-based composite material intermediate.
[0125] Example 5
[0126] The example is basically the same as Example 2, except that step (2) of Example 5 is as follows:
[0127] (2) The mixed powder obtained in step (1) is placed into a pulse current assisted pressing mold and sealed. An external pressure of 60 MPa is applied to perform the first pulse current assisted molding process. The pulse current intensity is adjusted to 5 A, the duty cycle is 0.3, the frequency is 100 Hz, and the current is continuously applied for 60 s to obtain the titanium-based composite material precursor. The pulse current intensity is adjusted to 15 A, and the current is continuously applied for 300 s to continue the second pulse current assisted molding process on the obtained titanium-based composite material precursor (i.e., in the second pulse current assisted molding process, the external pressure is 60 MPa, the duty cycle is 0.3, and the frequency is 100 Hz) to obtain the titanium-based composite material intermediate.
[0128] Example 6
[0129] The example is basically the same as Example 3, except that in Example 6, the mass of graphene accounts for 0.3 wt% of the mass of the titanium-based composite material.
[0130] Example 7
[0131] It is basically the same as Example 3, except that in Example 7, the mass of graphene accounts for 3 wt% of the mass of the titanium-based composite material.
[0132] Example 8
[0133] (1) According to the mass of graphene accounting for 1 wt% of the mass of titanium-based composite material, graphene powder, titanium material (pure titanium) powder and alcohol (the total mass of graphene powder and titanium material powder to the mass ratio of alcohol is 1:1) are mechanically mixed for 2 hours and then vacuum dried at 60°C to obtain a mixed powder containing graphene and titanium material.
[0134] (2) The mixed powder obtained in step (1) is placed into a pulse current assisted pressing mold and sealed. An external pressure of 60 MPa is applied to perform the first pulse current assisted molding process. The pulse current intensity is adjusted to 5 A, the duty cycle is 0.3, the frequency is 100 Hz, and the current is continuously applied for 300 s to obtain the titanium-based composite material precursor. The pulse current intensity is adjusted to 20 A, and the current is continuously applied for 300 s to continue the second pulse current assisted molding process on the obtained titanium-based composite material precursor (i.e., in the second pulse current assisted molding process, the external pressure is 60 MPa, the duty cycle is 0.3, and the frequency is 100 Hz) to obtain the titanium-based composite material intermediate.
[0135] (3) The titanium-based composite intermediate obtained in step (2) is forged at a forging temperature of 1000℃ and a forging ratio of 4. After forging, it is annealed at 750℃ for 2 h.
[0136] Comparative Example 1
[0137] The method is basically the same as that in Example 1, except that step (2) of Comparative Example 1 uses a hot pressing sintering method, as follows:
[0138] The mixed powder obtained in step (1) of Example 1 was subjected to hot pressing sintering method, with an external pressure of 60 MPa, a temperature of 1050℃, and a holding time of 0.5 h to obtain a titanium-based composite intermediate; then the obtained titanium-based composite intermediate was forged at a forging temperature of 1050℃ and a forging ratio of 4, and annealed at 750℃ for 2 h after forging.
[0139] Comparative Example 2
[0140] (1) According to the mass of titanium carbide powder accounting for 1 wt% of the mass of titanium-based composite material, titanium material (TC4 titanium alloy) powder, titanium carbide powder and alcohol (the total mass of titanium carbide powder and titanium material powder to the mass ratio of alcohol is 1:1) are mechanically mixed for 2 h and then vacuum dried at 60℃ to obtain a mixed powder containing titanium carbide powder and titanium material.
[0141] (2) The mixed powder obtained in step (1) is placed into a pulse current assisted pressing mold and sealed. An external pressure of 60 MPa is applied to perform the first pulse current assisted molding treatment. The pulse current intensity is adjusted to 5 A, the duty cycle is 0.1, the frequency is 100 Hz, and the current is continuously applied for 60 s to obtain the titanium-based composite material precursor. The pulse current intensity is adjusted to 10 A, and the current is continuously applied for 300 s to continue the second pulse current assisted molding treatment on the obtained titanium-based composite material precursor (i.e., in the second pulse current assisted molding treatment, the external pressure is 60 MPa, the duty cycle is 0.1, and the frequency is 100 Hz) to obtain the titanium-based composite material intermediate.
[0142] (3) The titanium-based composite material intermediate obtained in step (2) is forged at a forging temperature of 1050℃ and a forging ratio of 4. After forging, it is annealed at 750℃ for 2 h to obtain the titanium-based composite material.
[0143] Comparative Example 3
[0144] The results are basically the same as in Example 1, except that in Comparative Example 3, the current intensity of the first pulse current assisted molding process is 15 A.
[0145] Comparative Example 4
[0146] The process is basically the same as in Example 1, except that in Comparative Example 4, the current intensity of the second pulse current-assisted molding process is 5 A.
[0147] Comparative Example 5
[0148] The method is basically the same as that in Example 8, except that step (2) of Comparative Example 5 uses a hot pressing sintering method, as follows:
[0149] The mixed powder obtained in step (1) of Example 8 was subjected to hot pressing sintering method, with an external pressure of 60 MPa, a temperature of 1050℃, and a holding time of 0.5 h to obtain a titanium-based composite material intermediate; then the obtained titanium-based composite material intermediate was forged at a forging temperature of 1050℃ and a forging ratio of 4, and annealed at 750℃ for 2 h after forging.
[0150] Some parameters of the preparation methods of the titanium-based composite materials in the examples and comparative examples are shown in Table 1.
[0151] Table 1
[0152]
[0153] Referring to GB / T 228.1-2021, the tensile strength, yield strength and elongation of the graphene aluminum matrix composites prepared in each example and comparative example were tested, and the results are shown in Table 2.
[0154] Table 2
[0155]
[0156] As shown in Table 2, compared to Comparative Examples 1-4, the titanium-based composite materials obtained by sequentially performing first-pulse current-assisted molding treatment and second-pulse current-assisted molding treatment on the mixed powders containing graphene powder and TC4 titanium alloy powder in Examples 1-7 with specific current intensities exhibit better plasticity and higher tensile strength, yield strength, and elastic modulus. Compared to Comparative Example 5, the titanium-based composite material obtained by sequentially performing first-pulse current-assisted molding treatment and second-pulse current-assisted molding treatment on the mixed powders containing graphene powder and pure titanium powder in Example 8 with specific current intensities also exhibits better plasticity and higher tensile strength, yield strength, and elastic modulus.
[0157] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0158] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification and drawings can be used to interpret the content of the claims.
Claims
1. A method for preparing a titanium-based composite material, characterized in that, Includes the following steps: A mixed powder containing graphene and titanium materials is subjected to a first pulse current-assisted molding process to obtain a titanium-based composite material precursor; the mass of graphene accounts for 0.3 wt% to 3 wt% of the mass of the titanium-based composite material, and the current intensity of the first pulse current-assisted molding process is 5 A to 10 A; The titanium-based composite material precursor is subjected to a second pulse current-assisted molding treatment to obtain a titanium-based composite material intermediate; the current intensity of the second pulse current-assisted molding treatment is 10 A to 20 A. The titanium-based composite intermediate is subjected to thermoplastic deformation treatment; The applied compressive stress of the first pulse current assisted molding process and the second pulse current assisted molding process are independently 10 MPa~60 MPa, the pulse power supply frequency of the first pulse current assisted molding process and the second pulse current assisted molding process is independently 100 Hz~300 Hz, the pulse power supply duty cycle of the first pulse current assisted molding process and the second pulse current assisted molding process is independently 0.1~0.5, the time of the first pulse current assisted molding process is 60 s~300 s, and the time of the second pulse current assisted molding process is 300 s~420 s.
2. The preparation method according to claim 1, characterized in that, The current intensity of the second pulse current assisted molding process is greater than the current intensity of the first pulse current assisted molding process.
3. The preparation method according to claim 1, characterized in that, The current intensity of the first pulse current assisted molding process is 5 A to 8 A, and the current intensity of the second pulse current assisted molding process is 15 A to 20 A.
4. The preparation method according to claim 1, characterized in that, The preparation method satisfies at least one of the following features (1) to (3): (1) The external compressive stress of the first pulse current assisted molding process and the second pulse current assisted molding process are independently 30 MPa~60 MPa; (2) The pulse power supply frequencies of the first pulse current assisted molding process and the second pulse current assisted molding process are independently 100 Hz to 200 Hz; (3) The duty cycle of the pulse power supply for the first pulse current assisted molding process and the second pulse current assisted molding process is 0.3~0.5 independently.
5. The preparation method according to claim 1, characterized in that, The graphene accounts for 0.3 wt% to 2 wt% of the mass of the titanium-based composite material.
6. The preparation method according to any one of claims 1 to 5, characterized in that, The titanium material includes at least one of pure titanium and titanium alloys.
7. The preparation method according to any one of claims 1 to 5, characterized in that, The preparation of the mixed powder includes the following steps: The graphene powder, titanium powder, and organic solvent are mixed and stirred, then dried to obtain the mixed powder.
8. The preparation method according to any one of claims 1 to 5, characterized in that, The thermoplastic deformation treatment satisfies at least one of the following characteristics (1) to (2): (1) The thermoplastic deformation treatment method includes one of hot extrusion, forging and rolling; (2) The thermoplastic deformation treatment is carried out by forging, the forging temperature is 1000℃~1100℃, and the forging ratio is 3~5.
9. A titanium-based composite material, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 8.
10. A titanium-based product, characterized in that, Including the titanium-based composite material as described in claim 9.
Citation Information
Patent Citations
Highly thermally conductive composite material
CN101743337A
Graphene-reinforced titanium-based composite and preparation method thereof
CN104846227A